Film, laminate, and wiring board
Patent Information
- Application Number
- JP2023140488
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0008】 本開示の一実施形態によれば、段差追従性及び耐熱性に優れるフィルム、積層体、及び配線基板が提供される。
Smart Images

Figure 2025034226000001 
Figure 2025034226000002 
Figure 2025034226000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a film, a laminate, and a wiring board. [Background technology]
[0002] In recent years, the frequencies used in communication devices have tended to become very high. In order to suppress transmission loss in the high frequency band, it is required to lower the relative dielectric constant and dielectric loss tangent of insulating materials used in circuit boards. Copper-clad laminates are preferably used as components constituting circuit boards, and films are preferably used to manufacture copper-clad laminates.
[0003] For example, Patent Document 1 describes a polymer film having a layer A and a layer B on at least one side of the layer A, the layer A containing a polymer having a dielectric loss tangent of 0.01 or less, the layer B containing an additive, and the layer B having an inflection point in the change in elastic modulus with temperature change or deformation speed change, or the elastic modulus decreases under pressure. Patent Document 2 describes a liquid crystal polymer film containing a liquid crystal polymer component and at least one component selected from the group consisting of an olefin component, a crosslinking component, and a compatible component. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2022 / 163776 [Patent Document 2] International Publication No. 2021 / 060455 Summary of the Invention [Problem to be solved by the invention]
[0005] Usually, a copper-clad laminate is manufactured by laminating a copper foil on the surface of a polymer film. A wiring board is manufactured by stacking a copper-clad laminate and a wiring substrate so that the polymer film of the copper-clad laminate and the wiring substrate are in contact with each other. When manufacturing a wiring board, it is required that the polymer film deforms to conform to the steps formed on the surface of the wiring substrate from the viewpoint of adhesion. On the other hand, when a polymer film with excellent step conformability to a wiring substrate is used for a copper-clad laminate, delamination may occur during the reflow soldering process performed when mounting electronic components. For this reason, there has been a demand for a material that has both step conformability to a wiring substrate and excellent adhesion during reflow soldering (i.e., excellent heat resistance).
[0006] An object of one embodiment of the present disclosure is to provide a film, a laminate, and a wiring board that are excellent in step conformability and heat resistance. [Means for solving the problem]
[0007] Means for solving the above problems include the following aspects. <1> having a phase-separated structure containing at least two phases, The elastic modulus at 160°C is 0.60 MPa or less, The elastic modulus G1 at 260°C of the first phase, which is one of the at least two phases, is greater than 0.10 MPa; The elastic modulus G2 at 260°C of the second phase different from the first phase is 0.10 MPa or less, In a cross section along the thickness direction of the film, the number of regions in the second phase whose length in the thickness direction is 20 μm or more is 140 / mm 2 Below is the film. <2> The second phase comprises a polymer having a weight average molecular weight of 1000 or more. <1> The film according to claim 1. <3> The polymer having a weight average molecular weight of 1000 or more is a thermoplastic elastomer. <2> The film according to claim 1. <4> The thermoplastic elastomer is an elastomer containing structural units derived from styrene. <3> The film according to claim 1. <5> The thermoplastic elastomer is at least one selected from the group consisting of styrene-ethylene-butylene-styrene block copolymers, styrene-isobutylene-styrene block copolymers, styrene-ethylene-propylene-styrene copolymers, styrene-isoprene-styrene block copolymers, and hydrogenated products thereof. <3> The film according to claim 1. <6> In a cross section along the thickness direction of the film, the ratio of the second phase is 50% by area or more. <1> ~ <5> 13. The film according to claim 12, <7> A layer A and a layer B disposed on at least one surface of the layer A, Layer B has a phase-separated structure including at least two phases, The elastic modulus of layer B at 160°C is 0.60 MPa or less, The elastic modulus G1 at 260°C of the first phase, which is one of the at least two phases, is greater than 0.10 MPa; The elastic modulus G2 at 260°C of the second phase different from the first phase is 0.10 MPa or less, In a cross section along the thickness direction of layer B, the number of regions in the second phase having a length in the thickness direction of 20 μm or more is 140 / mm 2 The laminate is as follows: <8> Layer A comprises a liquid crystal polymer; <7> The laminate according to claim 1. <9> The present invention comprises a substrate, a wiring pattern disposed on at least one surface of the substrate, a layer B disposed between the wiring patterns and on the wiring patterns, and a layer A disposed on the layer B, Layer B has a phase-separated structure including at least two phases, The elastic modulus of layer B at 160°C is 0.60 MPa or less, The elastic modulus G1 at 260°C of the first phase, which is one of the at least two phases, is greater than 0.10 MPa; The elastic modulus G2 at 260°C of the second phase different from the first phase is 0.10 MPa or less, In a cross section along the thickness direction of layer B, the number of regions in the second phase having a length in the thickness direction of 20 μm or more is 140 / mm 2 The wiring board is shown below. Effect of the Invention
[0008] According to one embodiment of the present disclosure, a film, a laminate, and a wiring board having excellent step conformability and heat resistance are provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The contents of the present disclosure will be described in detail below. The following description of the components may be based on a representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment. In this specification, the use of "to" indicating a numerical range means that the numerical values before and after it are included as the lower limit and upper limit. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In addition, in the description of groups (atomic groups) in this specification, descriptions that do not indicate whether they are substituted or unsubstituted include those that have no substituents as well as those that have a substituent. For example, an "alkyl group" includes not only an alkyl group that has no substituents (unsubstituted alkyl groups) but also an alkyl group that has a substituent (substituted alkyl groups). In this specification, "(meth)acrylic" is a term used as a concept including both acrylic and methacrylic, and "(meth)acryloyl" is a term used as a concept including both acryloyl and methacryloyl. In addition, the term "process" in this specification includes not only an independent process but also a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved. Furthermore, in the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In addition, unless otherwise specified, the weight average molecular weight (Mw) and number average molecular weight (Mn) in the present disclosure are molecular weights detected by a gel permeation chromatography (GPC) analyzer using a column of TSKgel SuperHM-H (product name of Tosoh Corporation) in a solvent of PFP (pentafluorophenol) / chloroform = 1 / 2 (mass ratio) and a differential refractometer, and converted using polystyrene as a standard substance. The average particle size (e.g., D50) of the particles in the present disclosure is measured using a laser diffraction / scattering type particle size distribution measuring device, such as LA-950V2 manufactured by HORIBA Corporation.
[0010] [film] The film according to the present disclosure has a phase-separated structure including at least two phases, and has an elastic modulus at 160°C of 0.60 MPa or less, an elastic modulus G1 at 260°C of a first phase, which is one of the at least two phases, exceeds 0.10 MPa, and an elastic modulus G2 at 260°C of a second phase different from the first phase is 0.10 MPa or less, and in a cross section along the thickness direction of the film, the number of regions in the second phase having a length in the thickness direction of 20 μm or more is 140 / mm 2 The following is the result.
[0011] As a result of extensive investigations, the present inventors have found that the above-mentioned configuration makes it possible to provide a laminate having excellent step conformability and heat resistance. Although the detailed mechanism by which the above effects are obtained is unclear, it is speculated as follows.
[0012] When manufacturing a multi-layer copper-clad laminate, copper foil and film are laminated and then thermocompression bonded. During this process, some of the materials contained in the film become more fluid due to heating. During thermocompression bonding, some of the fluid materials may move within the film. This movement causes the fluid materials to aggregate. In the reflow soldering process performed when mounting electronic components, heating is performed at a high temperature (e.g., 260°C). During this process, it is believed that the water contained within the film becomes supersaturated and diffuses, causing bubble nuclei to form in the aggregated parts of the fluid materials. In the past, the bubble nuclei grew and foamed, which could cause peeling between the film and the metal layer. In contrast, in the film according to the present disclosure, in a cross section along the thickness direction of the film, the number of regions in the second phase having a length in the thickness direction of 20 μm or more is 140 / mm 2 Since the thickness of the film is less than 100 μm, localized flow of the material contained in the film is suppressed during thermocompression bonding. It is believed that the generation and growth of bubble nuclei is suppressed during the reflow soldering process, and as a result, peeling between the film and the metal layer is suppressed. In other words, the heat resistance is excellent.
[0013] In contrast, Patent Documents 1 and 2 do not mention the number of regions of the second phase having a length in the thickness direction of 20 μm or more in a cross section along the thickness direction of the film.
[0014] The film according to the present disclosure will be described in detail below.
[0015] The film according to the present disclosure has a phase-separated structure containing at least two phases. In the present disclosure, the term "phase-separated structure" refers to a structure in which the film has at least two parts containing different components.
[0016] Examples of the phase-separated structure include a sea-island structure, a co-continuous structure, a cylindrical structure, and a lamellar structure. Among these, the phase-separated structure in the film according to the present disclosure is preferably a sea-island structure. The sea-island structure refers to a structure in which one of at least two phases forms a continuous phase and the other phase is present in a discontinuously dispersed state.
[0017] The presence of a phase-separated structure can be confirmed by using means such as morphological observation, material distribution evaluation, mechanical property distribution evaluation, etc., for the film surface, film cross section, or both the film surface and cross section. In the present disclosure, if two different phase states of an area can be confirmed by any one of the methods of morphological observation, material distribution evaluation, and mechanical property distribution evaluation, it is determined that the film has a phase-separated structure. The morphological observation is carried out using a known optical microscope. When the observation cannot be carried out using a known optical microscope, the observation is carried out using an electron microscope or the like. Material distribution evaluation is performed using infrared spectroscopy imaging. If infrared spectroscopy imaging is not possible, Raman spectroscopy imaging is used. If Raman spectroscopy imaging is not possible, X-ray photoelectron spectroscopy imaging is used. The mechanical property distribution is evaluated using an atomic force microscope or the like.
[0018] <Phase 1> The film according to the present disclosure has a phase-separated structure including at least two phases. At least one of the two phases, that is, a first phase, has an elastic modulus G1 at 260° C. of more than 0.10 MPa.
[0019] In the present disclosure, the elastic modulus G1 of the first phase at 260° C. is measured by the following method. A film cross-section sample was prepared by obliquely cutting with a microtome so that the cross-section had a thickness of 50 μm. Next, the 260°C elastic modulus of the first phase is measured as the indentation elastic modulus by using a nanoindentation method. The indentation elastic modulus is measured by applying a load with a Vickers indenter at a loading rate of 0.28 mN / sec using a microhardness tester (e.g., product name "DUH-W201" manufactured by Shimadzu Corporation), holding the maximum load of 10 mN for 10 seconds, and then unloading at a loading rate of 0.28 mN / sec.
[0020] From the viewpoint of heat resistance, the elastic modulus of the first phase at 260° C. is preferably 0.15 MPa or more, more preferably 0.5 MPa or more, and even more preferably 1.0 MPa or more. The upper limit of the elastic modulus of the first phase at 260° C. is not particularly limited, and is, for example, 1000 MPa. When the elastic modulus of the first phase exceeds 0.10 MPa at 260° C., the heat resistance is excellent. When the elastic modulus G1 of the first phase exceeds 0.10 MPa at 260° C., the fluidity of the film at 260° C. is suppressed, and the heat resistance is improved.
[0021] The first phase may be a low molecular weight compound or a high molecular weight compound, so long as the first phase has an elastic modulus at 260° C. of more than 0.10 MPa.
[0022] Examples of compounds constituting the first phase include liquid crystal polymers, fluororesins, polymers of compounds having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond, polyphenylene ether and modified products thereof, aromatic polyether ketone, phenol resins, epoxy resins, polyimides, cyanate resins, bismaleimide resins, triazine resins, and other thermosetting resins.
[0023] -Liquid crystal polymer- From the viewpoint of dielectric loss tangent, it is preferable that the first phase comprises a liquid crystal polymer.
[0024] The type of liquid crystal polymer is not particularly limited, and any known liquid crystal polymer can be used. The liquid crystal polymer may be a thermotropic liquid crystal polymer that exhibits liquid crystallinity in a molten state, or a lyotropic liquid crystal polymer that exhibits liquid crystallinity in a solution state. In the case of a thermotropic liquid crystal, it is preferable that the liquid crystal polymer melts at a temperature of 450° C. or less.
[0025] Examples of liquid crystal polymers include liquid crystal polyester, liquid crystal polyester amide in which an amide bond is introduced into a liquid crystal polyester, liquid crystal polyester ether in which an ether bond is introduced into a liquid crystal polyester, and liquid crystal polyester carbonate in which a carbonate bond is introduced into a liquid crystal polyester.
[0026] From the viewpoint of liquid crystallinity, the liquid crystal polymer is preferably a polymer having an aromatic ring, and more preferably an aromatic polyester or an aromatic polyester amide.
[0027] Furthermore, the liquid crystal polymer may be a polymer in which an isocyanate-derived bond such as an imide bond, a carbodiimide bond, or an isocyanurate bond is further introduced into an aromatic polyester or an aromatic polyester amide.
[0028] The liquid crystal polymer is preferably a wholly aromatic liquid crystal polymer made using only aromatic compounds as raw material monomers.
[0029] Examples of the liquid crystal polymer include the following liquid crystal polymers. 1) (i) A compound obtained by polycondensation of an aromatic hydroxycarboxylic acid, (ii) an aromatic dicarboxylic acid, and (iii) at least one compound selected from the group consisting of an aromatic diol, an aromatic hydroxyamine, and an aromatic diamine. 2) Those obtained by polycondensation of multiple types of aromatic hydroxycarboxylic acids. 3) (i) a polycondensation product of an aromatic dicarboxylic acid and (ii) at least one compound selected from the group consisting of an aromatic diol, an aromatic hydroxyamine, and an aromatic diamine. 4) (i) Polyester such as polyethylene terephthalate and (ii) aromatic hydroxycarboxylic acid are polycondensed. Here, the aromatic hydroxycarboxylic acid, aromatic dicarboxylic acid, aromatic diol, aromatic hydroxyamine and aromatic diamine are each independently replaced with a derivative capable of polycondensation. It may be possible.
[0030] The melting point of the liquid crystal polymer is preferably higher than 260°C, more preferably higher than 260°C and 350°C or lower, and further preferably higher than 260°C and 330°C or lower.
[0031] In the present disclosure, the melting point is measured using a differential scanning calorimeter. For example, it is measured using a product named "DSC-60A Plus" (manufactured by Shimadzu Corporation). The temperature rise rate in the measurement is 10°C / min.
[0032] The weight average molecular weight of the liquid crystal polymer is preferably 1,000,000 or less, more preferably 3,000 to 300,000, further preferably 5,000 to 100,000, and particularly preferably 5,000 to 30,000.
[0033] From the viewpoint of further reducing the dielectric tangent, the liquid crystal polymer preferably contains an aromatic polyesteramide. The aromatic polyesteramide is a resin having at least one aromatic ring and having an ester bond and an amide bond. Among them, from the viewpoint of heat resistance, the aromatic polyesteramide is preferably a wholly aromatic polyesteramide.
[0034] The aromatic polyesteramide is preferably a crystalline polymer. The first phase preferably contains a crystalline aromatic polyesteramide. The aromatic polyesteramide being crystalline has a lower dielectric loss tangent. The term "crystalline polymer" refers to a polymer that has a clear endothermic peak, not a stepwise change in endothermic amount, in differential scanning calorimetry (DSC). Specifically, for example, it means that the half-width of the endothermic peak is within 10°C when measured at a heating rate of 10°C / min. Polymers with a half-width exceeding 10°C and polymers without a clear endothermic peak are classified as amorphous polymers and are distinguished from crystalline polymers.
[0035] The aromatic polyester amide preferably contains a constitutional unit represented by the following formula 1, a constitutional unit represented by the following formula 2, and a constitutional unit represented by the following formula 3. -O-Ar 1 -CO- …Formula 1 -CO-Ar 2 -CO- …Formula 2 -NH-Ar 3 -O- …Formula 3 In formulas 1 to 3, Ar 1 , Ar 2 , and Ar 3 each independently represents a phenylene group, a naphthylene group, or a biphenylylene group. Hereinafter, the structural unit represented by formula 1 will also be referred to as "unit 1", etc.
[0036] The unit 1 can be introduced, for example, by using an aromatic hydroxycarboxylic acid as a raw material. The unit 2 can be introduced, for example, by using an aromatic dicarboxylic acid as a raw material. Unit 3 can be introduced, for example, by using an aromatic hydroxylamine as a starting material.
[0037] Here, the aromatic hydroxycarboxylic acid, aromatic dicarboxylic acid, aromatic diol, and aromatic hydroxylamine may each independently be replaced with a derivative capable of undergoing polycondensation.
[0038] For example, aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids can be replaced with aromatic hydroxycarboxylic acid esters and aromatic dicarboxylic acid esters by converting the carboxy group to an alkoxycarbonyl group or an aryloxycarbonyl group. Aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids can be replaced with aromatic hydroxycarboxylic acid halides and aromatic dicarboxylic acid halides by converting the carboxy groups to haloformyl groups. Aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids can be replaced with aromatic hydroxycarboxylic acid anhydrides and aromatic dicarboxylic acid anhydrides by converting the carboxy groups to acyloxycarbonyl groups. Examples of polycondensable derivatives of compounds having a hydroxy group, such as aromatic hydroxycarboxylic acids and aromatic hydroxyamines, include those obtained by acylation of a hydroxy group into an acyloxy group (acylated products). For example, aromatic hydroxycarboxylic acids and aromatic hydroxylamines can be replaced with their acylated counterparts by acylation of the hydroxy group to convert it to an acyloxy group. Examples of the polycondensable derivatives of aromatic hydroxylamines include those obtained by acylation of the amino group to an acylamino group (acylated product). For example, aromatic hydroxyamines can be replaced with acylated products by acylation of the amino group to convert them to acylamino groups.
[0039] In formula 1, Ar 1 is preferably a p-phenylene group, a 2,6-naphthylene group, or a 4,4'-biphenylylene group, and more preferably a 2,6-naphthylene group.
[0040] Ar 1 When is a p-phenylene group, unit 1 is, for example, a constitutional unit derived from p-hydroxybenzoic acid. Ar 1is a 2,6-naphthylene group, unit 1 is, for example, a constitutional unit derived from 6-hydroxy-2-naphthoic acid. Ar 1 When is a 4,4'-biphenylylene group, unit 1 is, for example, a constitutional unit derived from 4'-hydroxy-4-biphenylcarboxylic acid.
[0041] In formula 2, Ar 2 is preferably a p-phenylene group, an m-phenylene group, or a 2,6-naphthylene group, and more preferably an m-phenylene group.
[0042] Ar 2 When is a p-phenylene group, unit 2 is, for example, a constitutional unit derived from terephthalic acid. Ar 2 When is an m-phenylene group, unit 2 is, for example, a constitutional unit derived from isophthalic acid. Ar 2 is a 2,6-naphthylene group, unit 2 is, for example, a constitutional unit derived from 2,6-naphthalenedicarboxylic acid.
[0043] In formula 3, Ar 3 is preferably a p-phenylene group or a 4,4'-biphenylylene group, and more preferably a p-phenylene group.
[0044] Ar 3 When is a p-phenylene group, unit 3 is, for example, a constitutional unit derived from p-aminophenol. Ar 3 is a 4,4'-biphenylylene group, unit 3 is, for example, a constitutional unit derived from 4-amino-4'-hydroxybiphenyl.
[0045] With respect to the total content of units 1, 2, and 3, the content of units 1 is preferably 30 mol% or more, the content of units 2 is preferably 35 mol% or less, and the content of units 3 is preferably 35 mol% or less. The content of unit 1 is more preferably 30 mol % to 80 mol %, further preferably 30 mol % to 60 mol %, and particularly preferably 30 mol % to 40 mol %, based on the total content of unit 1, unit 2, and unit 3. The content of unit 2 is preferably 10 mol % to 35 mol %, more preferably 20 mol % to 35 mol %, and particularly preferably 30 mol % to 35 mol %, based on the total content of unit 1, unit 2, and unit 3. The content of unit 3 is preferably 10 mol % to 35 mol %, more preferably 20 mol % to 35 mol %, and particularly preferably 30 mol % to 35 mol %, based on the total content of unit 1, unit 2, and unit 3. The total content of each structural unit is the sum of the amounts (moles) of each structural unit, which is calculated by dividing the mass of each structural unit constituting the aromatic polyesteramide by the formula weight of the structural unit.
[0046] The ratio of the content of units 2 to the content of units 3, expressed as [content of units 2] / [content of units 3] (mol / mol), is preferably 0.9 / 1 to 1 / 0.9, more preferably 0.95 / 1 to 1 / 0.95, and even more preferably 0.98 / 1 to 1 / 0.98.
[0047] The aromatic polyesteramide may have two or more independent types of the units 1 to 3. The aromatic polyesteramide may have other structural units than the units 1 to 3. The content of the other structural units is preferably 10 mol % or less, more preferably 5 mol % or less, based on the total content of all the structural units.
[0048] The aromatic polyesteramide is preferably produced by melt-polymerizing raw material monomers corresponding to the structural units constituting the aromatic polyesteramide.
[0049] The weight average molecular weight of the aromatic polyesteramide is preferably 1,000,000 or less, more preferably 3,000 to 300,000, further preferably 5,000 to 100,000, and particularly preferably 5,000 to 30,000.
[0050] -Fluoroplastics- The polymer contained in the first phase may be a fluororesin from the viewpoints of heat resistance and mechanical strength.
[0051] In the present disclosure, the type of fluororesin is not particularly limited, and any known fluororesin can be used.
[0052] Fluorine resins include homopolymers and copolymers that contain constitutional units derived from fluorinated α-olefin monomers, i.e., α-olefin monomers that contain at least one fluorine atom, and also include copolymers that contain constitutional units derived from fluorinated α-olefin monomers and constitutional units derived from non-fluorinated ethylenically unsaturated monomers that are reactive with the fluorinated α-olefin monomers.
[0053] Fluorinated α-olefin monomers include CF2=CF2, CHF=CF2, CH2=CF2, CHCl=CHF, CClF=CF2, CCl2=CF2, CClF=CClF, CHF=CCl2, CH2=CClF, CCl2=CClF, CF3CF=CF2, CF3CF=CHF, CF3CH=CF2, CF3CH=CH2, CHF2CH=CHF, CF3CF=CF2, and perfluoro(alkyl having 2 to 8 carbon atoms)vinyl ethers (e.g., perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, and perfluorooctyl vinyl ether). Among them, the fluorinated α-olefin monomer is preferably at least one monomer selected from the group consisting of tetrafluoroethylene (CF2=CF2), chlorotrifluoroethylene (CClF=CF2), (perfluorobutyl)ethylene, vinylidene fluoride (CH2=CF2), and hexafluoropropylene (CF2=CFCF3). Non-fluorinated ethylenically unsaturated monomers include ethylene, propylene, butene, ethylenically unsaturated aromatic monomers (eg, styrene and α-methylstyrene), and the like. The fluorinated α-olefin monomers may be used alone or in combination of two or more kinds. The non-fluorinated ethylenically unsaturated monomers may be used alone or in combination of two or more kinds.
[0054] Examples of fluororesins include polychlorotrifluoroethylene (PCTFE), poly(chlorotrifluoroethylene-propylene), poly(ethylene-tetrafluoroethylene) (ETFE), poly(ethylene-chlorotrifluoroethylene) (ECTFE), poly(hexafluoropropylene), poly(tetrafluoroethylene) (PTFE), poly(tetrafluoroethylene-ethylene-propylene), poly(tetrafluoroethylene-hexafluoropropylene) (FEP), poly(tetrafluoroethylene-propylene) (FEPM), poly(tetrafluoroethylene-perfluoropropylene vinyl ether), poly(tetrafluoroethylene-perfluoroalkyl vinyl ether) (PFA) (e.g., poly(tetrafluoroethylene-perfluoropropyl vinyl ether)), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), poly(vinylidene fluoride-chlorotrifluoroethylene), perfluoropolyether, perfluorosulfonic acid, and perfluoropolyoxetane.
[0055] The fluororesin may have structural units derived from fluorinated ethylene or fluorinated propylene. The fluororesin may be used alone or in combination of two or more kinds.
[0056] The fluororesin is preferably FEP, PFA, ETFE or PTFE. FEP is available from DuPont under the trade name TEFLON FEP, or from Daikin Industries, Ltd. under the trade name NEOFLON FEP. PFA is available from Daikin Industries, Ltd. under the trade name NEOFLON PFA, from DuPont under the trade name TEFLON PFA, or from Solvay Solexis under the trade name HYFLON PFA.
[0057] More preferably, the fluororesin comprises PTFE. The PTFE may be a PTFE homopolymer, a partially modified PTFE homopolymer, or a combination comprising one or both of these. The partially modified PTFE homopolymer preferably comprises less than 1% by mass of units derived from comonomers other than tetrafluoroethylene, based on the total mass of the polymer.
[0058] The fluororesin may be a crosslinkable fluoropolymer having a crosslinkable group. The crosslinkable fluoropolymer can be crosslinked by a conventionally known crosslinking method. One representative crosslinkable fluoropolymer is a fluoropolymer having (meth)acryloyloxy. For example, the crosslinkable fluoropolymer is Formula:H2C=CR'COO-(CH2) n -R-(CH2) n -OOCR'=CH2 In the formula, R is an oligomer chain containing a constituent unit derived from a fluorinated α-olefin monomer, R' is H or -CH3, and n is 1 to 4. R may be a fluorine-based oligomer chain containing a constituent unit derived from tetrafluoroethylene.
[0059] A crosslinked fluoropolymer network can be formed by exposing a fluoropolymer having (meth)acryloyloxy groups to a free radical source to initiate a radical crosslinking reaction via the (meth)acryloyloxy groups on the fluororesin. The free radical source is not particularly limited, but preferably includes a photoradical polymerization initiator or an organic peroxide. Suitable photoradical polymerization initiators and organic peroxides are well known in the art. Crosslinkable fluoropolymers are commercially available, such as Viton B manufactured by DuPont.
[0060] -Polymer of a compound having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond- The polymer contained in the first phase may be a polymer of a compound having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond.
[0061] Examples of polymers of compounds having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond include thermoplastic resins having structural units derived from cyclic olefin monomers such as norbornene or polycyclic norbornene monomers.
[0062] The polymer of the compound having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond may be a ring-opening polymer of the above-mentioned cyclic olefin or a hydrogenated product of a ring-opening copolymer using two or more kinds of cyclic olefins, or may be an addition polymer of a cyclic olefin and an aromatic compound having an ethylenically unsaturated bond such as a chain olefin or a vinyl group. A polar group may be introduced into the polymer of the compound having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond.
[0063] The polymer of a compound having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond may be used alone or in combination of two or more kinds.
[0064] The ring structure of the cyclic aliphatic hydrocarbon group may be a monocyclic ring, a condensed ring in which two or more rings are condensed, or a bridged ring. Examples of the ring structure of the cyclic aliphatic hydrocarbon group include a cyclopentane ring, a cyclohexane ring, a cyclooctane ring, an isophorone ring, a norbornane ring, and a dicyclopentane ring. The compound having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond is not particularly limited, and may be a (meth)acrylate compound having a cyclic aliphatic hydrocarbon group, a (meth)acrylamide compound having a cyclic aliphatic hydrocarbon group, or a vinyl compound having a cyclic aliphatic hydrocarbon group. Among them, a (meth)acrylate compound having a cyclic aliphatic hydrocarbon group is preferred. In addition, the compound having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond may be a monofunctional ethylenically unsaturated compound or a polyfunctional ethylenically unsaturated compound. The number of cycloaliphatic hydrocarbon groups in a compound having a cycloaliphatic hydrocarbon group and a group having an ethylenically unsaturated bond may be one or more, and may be two or more. The polymer of a compound having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond may be a polymer obtained by polymerizing at least one compound having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond, and may be a polymer of a compound having two or more types of cyclic aliphatic hydrocarbon groups and a group having an ethylenically unsaturated bond, or may be a copolymer with another ethylenically unsaturated compound that does not have a cyclic aliphatic hydrocarbon group. The polymer of a compound having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond is preferably a cycloolefin polymer.
[0065] -Polyphenylene ether- The polymer in the first phase may be a polyphenylene ether. The polyphenylene ether preferably has an average number of phenolic hydroxyl groups at the molecular terminals (number of terminal hydroxyl groups) per molecule of 1 to 5, and more preferably 1.5 to 3, from the viewpoints of dielectric tangent and heat resistance. The number of terminal hydroxyl groups of polyphenylene ether can be known from, for example, the specification value of the polyphenylene ether product. The number of terminal hydroxyl groups is expressed, for example, as the average number of phenolic hydroxyl groups per molecule of all polyphenylene ethers present in 1 mole of polyphenylene ether. The polyphenylene ether may be used alone or in combination of two or more kinds.
[0066] Examples of polyphenylene ether include polyphenylene ether composed of 2,6-dimethylphenol and at least one of a difunctional phenol and a trifunctional phenol, and poly(2,6-dimethyl-1,4-phenylene oxide). More specifically, the polyphenylene ether is preferably a compound having a structure represented by the formula (PPE).
[0067] [ka]
[0068] In formula (PPE), X represents an alkylene group having 1 to 3 carbon atoms or a single bond, m represents an integer of 0 to 20, n represents an integer of 0 to 20, and the sum of m and n represents an integer of 1 to 30. The alkylene group in X may, for example, be a dimethylmethylene group.
[0069] When the polyphenylene ether is thermally cured after film formation, from the viewpoints of heat resistance and film formability, the weight average molecular weight (Mw) is preferably 500 to 5,000, and more preferably 500 to 3,000. When the polyphenylene ether is not thermally cured, the weight average molecular weight (Mw) is not particularly limited, but is preferably 3,000 to 100,000, and more preferably 5,000 to 50,000.
[0070] -Aromatic polyether ketone- The polymer in the first phase may be an aromatic polyether ketone.
[0071] The aromatic polyether ketone is not particularly limited, and any known aromatic polyether ketone can be used.
[0072] The aromatic polyether ketone is preferably a polyether ether ketone.
[0073] Polyetheretherketone is a type of aromatic polyetherketone, and is a polymer in which bonds are arranged in the following order: ether bond, ether bond, and carbonyl bond. Each bond is preferably linked by a divalent aromatic group. The aromatic polyether ketones may be used alone or in combination of two or more kinds.
[0074] Examples of aromatic polyetherketones include polyetheretherketone (PEEK) having a chemical structure represented by the following formula (P1), polyetherketone (PEK) having a chemical structure represented by the following formula (P2), polyetherketoneketone (PEKK) having a chemical structure represented by the following formula (P3), polyetheretherketoneketone (PEEKK) having a chemical structure represented by the following formula (P4), and polyetherketoneetherketoneketone (PEKEKK) having a chemical structure represented by the following formula (P5).
[0075] [ka]
[0076] From the viewpoint of mechanical properties, n in each of the formulas (P1) to (P5) is preferably 10 or more, and more preferably 20 or more. On the other hand, from the viewpoint of easiness in producing the aromatic polyether ketone, n is preferably 5,000 or less, and more preferably 1,000 or less. That is, n is preferably 10 to 5,000, and more preferably 20 to 1,000.
[0077] Among these, from the viewpoint of dielectric tangent, the polymer contained in the first phase is preferably at least one selected from the group consisting of a liquid crystal polymer, a polymer of a compound having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond, and a fluororesin, and is more preferably an aromatic polyesteramide.
[0078] The first phase may contain components other than the above polymers as long as the effects of the present disclosure are not significantly impaired. As the other components, known additives can be used, such as a leveling agent, a defoaming agent, an antioxidant, an ultraviolet absorbing agent, a flame retardant, and a colorant.
[0079] (Phase 2) The film according to the present disclosure has a phase-separated structure including at least two phases. One of the at least two phases, which is a second phase different from the first phase, has an elastic modulus G2 at 260° C. of 0.10 MPa or less.
[0080] In the present disclosure, the elastic modulus G2 of the second phase at 260° C. is measured by the following method. A film cross-section sample was prepared by obliquely cutting with a microtome so that the cross-section had a thickness of 50 μm. Next, the 260°C elastic modulus of the second phase is measured as the indentation elastic modulus by using a nanoindentation method. The indentation elastic modulus is measured by applying a load with a Vickers indenter at a loading rate of 0.28 mN / sec using a microhardness tester (e.g., product name "DUH-W201" manufactured by Shimadzu Corporation), holding the maximum load of 10 mN for 10 seconds, and then unloading at a loading rate of 0.28 mN / sec.
[0081] From the viewpoint of conformability to unevenness, the elastic modulus of the second phase at 260° C. is preferably less than 0.10 MPa, more preferably 0.07 MPa or less, and even more preferably 0.05 MPa or less. The lower limit of the elastic modulus of the second phase at 260° C. is not particularly limited, and may be, for example, 0.1 kPa. When the elastic modulus of the second phase is 0.10 MPa or less at 260° C., the film has excellent step conformability. When the elastic modulus G2 at 260° C. is 0.10 MPa or less, the entire film becomes easily deformed, and the film has excellent step conformability.
[0082] The second phase may be a low molecular weight compound or a high molecular weight compound, so long as the modulus of elasticity at 260° C. is 0.10 MPa or less.
[0083] From the viewpoint of heat resistance, the second phase preferably contains a polymer having a weight average molecular weight of 1,000 or more.
[0084] The weight-average molecular weight of the polymer contained in the second phase is more preferably at least 10,000, and even more preferably at least 30,000. The upper limit of the weight-average molecular weight is, for example, 1,000,000.
[0085] From the viewpoint of conformability to unevenness, the polymer is preferably a thermoplastic resin, a thermoplastic elastomer, an uncured or semi-cured product of a thermosetting resin, or an uncured or semi-cured product of a thermosetting elastomer.
[0086] Examples of thermoplastic resins include polyurethane resins, polyester resins, (meth)acrylic resins, polystyrene resins, fluororesins, polyimide resins, fluorinated polyimide resins, polyamide resins, polyamideimide resins, polyetherimide resins, cellulose acylate resins, polyurethane resins, polyether ether ketone resins, polycarbonate resins, polyolefin resins (e.g., polyethylene resins, polypropylene resins, resins made of cyclic olefin copolymers, alicyclic polyolefin resins), polyarylate resins, polyethersulfone resins, polysulfone resins, fluorene ring-modified polycarbonate resins, alicyclic modified polycarbonate resins, and fluorene ring-modified polyester resins.
[0087] Examples of the thermoplastic elastomer include elastomers containing structural units derived from styrene (polystyrene-based elastomers), polyester-based elastomers, polyolefin-based elastomers, polyurethane-based elastomers, polyamide-based elastomers, polyacrylic-based elastomers, silicone-based elastomers, polyimide-based elastomers, etc. The thermoplastic elastomer may be a hydrogenated product.
[0088] Examples of polystyrene-based elastomers include styrene-butadiene-styrene block copolymers (SBS), styrene-isoprene-styrene block copolymers (SIS), polystyrene-poly(ethylene-propylene) diblock copolymers (SEP), polystyrene-poly(ethylene-propylene)-polystyrene triblock copolymers (SEPS), styrene-ethylene-butylene-styrene block copolymers (SEBS), and polystyrene-poly(ethylene / ethylene-propylene)-polystyrene triblock copolymers (SEEPS), styrene-isobutylene-styrene block copolymers (SIBS), and hydrogenated products thereof.
[0089] Among these, from the viewpoints of dielectric tangent and step-following ability, the polymer is preferably a thermoplastic elastomer, more preferably an elastomer containing a structural unit derived from styrene, and even more preferably at least one selected from the group consisting of a styrene-ethylene-butylene-styrene block copolymer, a styrene-isobutylene-styrene block copolymer, a styrene-ethylene-propylene-styrene copolymer, a styrene-isoprene-styrene block copolymer, and hydrogenated products thereof.
[0090] In particular, hydrogenated styrene-isobutylene-styrene block copolymers are advantageous in terms of heat resistance since they are unlikely to soften at high temperatures (eg, 260° C.).
[0091] From the viewpoint of achieving both step-following ability and processability, the proportion of the second phase in a cross section along the thickness direction of the film is preferably 50 area % or more, more preferably 50 area % to 95 area %, and even more preferably 60 area % to 90 area %.
[0092] The film according to the present disclosure has an elastic modulus of 0.60 MPa or less, preferably 0.50 MPa or less, at 160° C. When the elastic modulus at 160° C. is 0.60 MPa or less, the film has excellent step conformability. The lower limit of the elastic modulus at 160° C. is not particularly limited, but is 0.001 MPa from the viewpoint of preventing the components constituting the film from flowing and being pushed out of the system when pressure is applied.
[0093] In the present disclosure, the elastic modulus of a film at 160° C. is measured by the following method. A film cross-section sample was prepared by obliquely cutting with a microtome so that the cross-section had a thickness of 50 μm. Next, the elastic modulus of the film is measured as the indentation elastic modulus by using a nanoindentation method. The indentation elastic modulus is measured by applying a load at a loading rate of 0.28 mN / sec with a Vickers indenter using a microhardness tester (for example, product name "DUH-W201" manufactured by Shimadzu Corporation), holding the maximum load of 10 mN for 10 seconds, and then unloading at a loading rate of 0.28 mN / sec. The cross-sectional sample is measured at 20 arbitrary positions at 160°C, and the average value is taken as the elastic modulus.
[0094] In the film according to the present disclosure, in a cross section along the thickness direction of the film, the number of regions in the second phase having a length in the thickness direction of 20 μm or more is 140 / mm 2 When the number of regions having a length of 20 μm or more in the thickness direction is large, the fluidity in the thickness direction of the film is high. When the fluidity in the thickness direction of the film is high, the film tends to be pushed up in the thickness direction by air bubbles from inside the film, and the heat resistance tends to decrease. On the other hand, when the number of regions having a length of 20 μm or more in the thickness direction is 140 / mm 2 If the thickness is less than 100 nm, localized flow of the material contained in the film is suppressed during thermocompression bonding, and the generation and growth of bubble nuclei during the reflow soldering process is suppressed, resulting in excellent heat resistance.
[0095] From the viewpoint of further improving heat resistance, the number of regions having a length of 20 μm or more in the thickness direction is set to 140 / mm2 It is preferable that the number of pieces is 70 pieces / mm or less. 2 The lower limit of the number is not particularly limited, and is preferably 0 pieces / mm 2 may be also possible.
[0096] The number of portions of the second phase having a length of 20 μm or more in the thickness direction is measured by the following method.
[0097] The second phase is identified from the image obtained by X-ray CT scanning of the film. Among the identified second phases, the number of regions with a length of 20 μm or more in the thickness direction is counted. The measurement is performed at 0.05 mm 2 The measurement is carried out at three arbitrary points within the range. The average value is multiplied by 20 to obtain a value of 1 mm. 2 Convert into the number of pieces per unit.
[0098] The film according to the present disclosure preferably has a dielectric loss tangent of 0.01 or less, more preferably 0.005 or less, and even more preferably greater than 0 and 0.003 or less.
[0099] In this disclosure, the dielectric loss tangent is measured by the following method. The dielectric loss tangent is measured by the resonance perturbation method at a frequency of 10 GHz. A 10 GHz cavity resonator (Kanto Electronics Application Development Co., Ltd.'s "CP531") is connected to a network analyzer (Agilent Technology's "E8363B"), and the polymer film is inserted into the cavity resonator. The change in the resonance frequency is measured before and after insertion for 96 hours in an environment with a temperature of 25°C and a humidity of 60%.
[0100] The thickness of the film according to the present disclosure is preferably 6 μm to 200 μm, more preferably 12 μm to 100 μm, and particularly preferably 20 μm to 60 μm, from the viewpoints of strength, dielectric tangent, and adhesion to the metal layer.
[0101] The thickness of the film is measured at any five points using an adhesive thickness gauge, such as an electronic micrometer (product name "KG3001A", manufactured by Anritsu Corporation), and the average value of the measured thicknesses is used.
[0102] [Laminate] The laminate according to the present disclosure includes a layer A and a layer B disposed on at least one surface of the layer A, the layer B having a phase-separated structure including at least two phases, the elastic modulus of the layer B at 160° C. is 0.60 MPa or less, the elastic modulus G1 at 260° C. of a first phase, which is one of the at least two phases, exceeds 0.10 MPa, and the elastic modulus G2 at 260° C. of a second phase different from the first phase is 0.10 MPa or less, and in a cross section along the thickness direction of the layer B, the number of regions in the second phase having a length in the thickness direction of 20 μm or more is 140 / mm 2 The following is the result.
[0103] In the laminate according to the present disclosure, in a cross section along the thickness direction of Layer B, the number of regions in the second phase having a length in the thickness direction of 20 μm or more is 140 / mm 2 Since the thickness is less than or equal to 100 mm, it has excellent step conformability and heat resistance.
[0104] The laminate according to the present disclosure includes a layer A and a layer B disposed on at least one surface of the layer A. The layer A and the layer B may be in direct contact with each other, or another layer may be provided between the layer A and the layer B. From the viewpoints of step conformability and heat resistance, the layer A and the layer B are preferably in direct contact with each other.
[0105] <<Layer B>> Layer B has a phase-separated structure including at least two phases, and the elastic modulus G1 at 260°C of a first phase, which is one of the at least two phases, exceeds 0.10 MPa, and the elastic modulus G2 at 260°C of a second phase different from the first phase is 0.10 MPa or less.
[0106] Preferred embodiments of the first and second phases in layer B are the same as those of the first and second phases in the above film.
[0107] The elastic modulus of Layer B at 160° C. is 0.60 MPa or less, and preferably 0.50 MPa or less. When the elastic modulus of Layer B at 160° C. is 0.60 MPa or less, the layer has excellent conformability to unevenness. The lower limit of the elastic modulus of Layer B at 160° C. is not particularly limited, but may be 0.1 kPa from the viewpoint of processability.
[0108] In the present disclosure, the elastic modulus of Layer B at 160° C. is measured by the following method. A film cross-section sample was prepared by obliquely cutting with a microtome so that the cross-section had a thickness of 50 μm. Next, the elastic modulus of layer B is measured as the indentation elastic modulus by using a nanoindentation method. The indentation elastic modulus is measured by applying a load at a loading rate of 0.28 mN / sec with a Vickers indenter using a microhardness tester (for example, product name "DUH-W201" manufactured by Shimadzu Corporation), holding the maximum load of 10 mN for 10 seconds, and then unloading at a loading rate of 0.28 mN / sec. The cross-sectional sample is measured at 20 arbitrary positions at 160°C, and the average value is taken as the elastic modulus.
[0109] From the viewpoint of conformability to unevenness, the average thickness of Layer B is preferably from 5 μm to 50 μm, more preferably from 10 μm to 40 μm, and even more preferably from 15 μm to 30 μm.
[0110] <<Layer A>> The laminate according to the present disclosure has a layer A on which the above-mentioned layer B is provided.
[0111] From the viewpoint of making the dielectric loss tangent of the laminate equal to or less than 0.01, it is preferable that layer A contains a polymer having a dielectric loss tangent of 0.01 or less.
[0112] Layer A may contain only one type of polymer having a dielectric tangent of 0.01 or less, or may contain two or more types of polymers.
[0113] The dielectric tangent of a polymer having a dielectric tangent of 0.01 or less is preferably 0.005 or less, and more preferably more than 0 and 0.003 or less, from the viewpoint of the dielectric tangent of a polymer film.
[0114] Examples of polymers having a dielectric tangent of 0.01 or less include thermoplastic resins such as liquid crystal polymers, fluororesins, polymers of compounds having a cyclic aliphatic hydrocarbon group and a group having an ethylenically unsaturated bond, polyether ether ketone, polyolefin, polyamide, polyester, polyphenylene sulfide, polyether ketone, polycarbonate, polyether sulfone, polyphenylene ether and modified products thereof, and polyether imide; elastomers such as copolymers of glycidyl methacrylate and polyethylene; and thermosetting resins such as phenol resins, epoxy resins, polyimides, and cyanate resins.
[0115] From the viewpoint of the dielectric loss tangent of the polymer film, the polymer having a dielectric loss tangent of 0.01 or less is preferably a liquid crystal polymer. That is, it is preferable that Layer A contains a liquid crystal polymer. The preferred embodiment of the liquid crystal polymer is the same as the preferred embodiment of the liquid crystal polymer that may be contained in Layer B.
[0116] Layer A may contain a filler in addition to the polymer having a dielectric loss tangent of 0.01 or less. When Layer A contains a filler, the rigidity is improved and wiring distortion and the like can be suppressed.
[0117] The filler may be particulate or fibrous, and may be inorganic or organic particles. Specific examples of the inorganic and organic particles are as described above.
[0118] Layer A may contain only one type of filler, or may contain two or more types of fillers. When Layer A contains a filler, the content of the filler is preferably 30% by mass to 95% by mass, more preferably 50% by mass to 90% by mass, and particularly preferably 60% by mass to 80% by mass, relative to the total mass of Layer A, from the viewpoints of the dielectric tangent, heat resistance, and step-following ability of the laminate.
[0119] Layer A may contain additives other than the above-mentioned components. Preferred embodiments of other additives that may be contained in Layer A are the same as preferred embodiments of other additives that may be contained in Layer B.
[0120] Furthermore, the layer A may contain, as other additives, resins other than the polymer having a dielectric loss tangent of 0.01 or less. Examples of resins other than polymers having a dielectric tangent of 0.01 or less include thermoplastic resins other than liquid crystal polyesters, such as polypropylene, polyamide, polyesters other than liquid crystal polyesters, polyphenylene sulfide, polyether ketone, polycarbonate, polyether sulfone, polyphenylene ether and modified products thereof, and polyether imide; elastomers such as copolymers of glycidyl methacrylate and polyethylene; and thermosetting resins such as phenol resins, epoxy resins, polyimide resins, and cyanate resins.
[0121] The total content of other additives in Layer A is preferably 25 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of the content of the polymer having a dielectric tangent of 0.01 or less.
[0122] The elastic modulus of layer A at 160° C. is preferably more than 0.60 MPa, and more preferably 10 MPa or more. When the elastic modulus of layer A at 160° C. is more than 0.60 MPa, layer A can support layer B and has excellent step conformability. The upper limit of the elastic modulus of layer A at 160° C. is not particularly limited, but is 1000 MPa from the viewpoint of suppressing wiring distortion and the like.
[0123] In the present disclosure, the elastic modulus of Layer A at 160° C. is measured by the following method. A film cross-section sample was prepared by obliquely cutting with a microtome so that the cross-section had a thickness of 50 μm. Next, the elastic modulus of layer A is measured as the indentation elastic modulus using a nanoindentation method. The indentation elastic modulus is measured by applying a load at a loading rate of 0.28 mN / sec with a Vickers indenter using a microhardness tester (for example, product name "DUH-W201" manufactured by Shimadzu Corporation), holding the maximum load of 10 mN for 10 seconds, and then unloading at a loading rate of 0.28 mN / sec. The cross-sectional sample is measured at 20 arbitrary positions at 160°C, and the average value is taken as the elastic modulus.
[0124] The average thickness of layer A is not particularly limited, but from the viewpoints of the dielectric tangent, heat resistance, and suppression of wiring distortion of the laminate, it is preferably 5 μm to 90 μm, more preferably 10 μm to 70 μm, and particularly preferably 15 μm to 50 μm.
[0125] From the viewpoint of adhesion to a metal substrate, the laminate according to the present disclosure preferably further has a layer C in addition to the layer A and the layer B, and more preferably has the layer B, the layer A, and the layer C in this order.
[0126] <<Layer C>> Layer C is preferably an adhesive layer, that is, Layer C is preferably a surface layer (outermost layer).
[0127] From the viewpoint of dielectric loss tangent, the layer C preferably contains at least one polymer.
[0128] A preferred embodiment of the polymer used in the layer C is the same as a preferred embodiment of the polymer used in the layer A having a dielectric tangent of 0.01 or less.
[0129] The polymer contained in Layer C may be the same as or different from the polymer contained in Layer A or Layer B. From the viewpoint of adhesion between Layer A and Layer C, however, it is preferable that the polymer is the same as the polymer contained in Layer A.
[0130] Moreover, in order to bond the metal layer and the layer A, the layer C preferably contains an epoxy resin.
[0131] The epoxy resin is preferably a crosslinked product of a polyfunctional epoxy compound. The polyfunctional epoxy compound refers to a compound having two or more epoxy groups. The number of epoxy groups in the polyfunctional epoxy compound is preferably 2 to 4.
[0132] In particular, from the viewpoints of the dielectric tangent of the laminate and the adhesion to the metal layer, it is preferable that layer C contains an aromatic polyester amide and an epoxy resin.
[0133] The layer C may contain a filler. A preferred embodiment of the filler used in the layer C is the same as a preferred embodiment of the filler used in the layer A.
[0134] Layer C may contain additives other than those mentioned above. Preferred embodiments of the other additives used in Layer C are the same as those of the other additives used in Layer A, except as described below.
[0135] The average thickness of Layer C is preferably smaller than the average thickness of Layer A from the viewpoints of the dielectric tangent of the laminate and the adhesion to metals.
[0136] Average thickness T of layer A A and the average thickness T of layer C C T A / T C From the viewpoints of the dielectric tangent of the laminate and the adhesion to the metal layer, the value of is preferably greater than 1, more preferably 2 to 100, further preferably 2.5 to 20, and particularly preferably 3 to 10. Average thickness T of layer B B and the average thickness T of layer C C T B / T C From the viewpoints of the dielectric tangent of the laminate and the adhesion to the metal layer, the value of is preferably greater than 1, more preferably 2 to 100, further preferably 2.5 to 20, and particularly preferably 3 to 10.
[0137] Furthermore, from the viewpoints of the dielectric tangent of the laminate and the adhesion to the metal layer, the average thickness of Layer C is preferably 0.1 μm to 20 μm, more preferably 0.5 μm to 15 μm, even more preferably 1 μm to 10 μm, and particularly preferably 2 μm to 8 μm.
[0138] The method for measuring the average thickness of each layer in the laminate is as follows.
[0139] The laminate is cut in a plane perpendicular to the plane direction of the laminate, the thickness is measured at five or more points on the cross section, and the average value of the measurements is taken as the average thickness.
[0140] The laminate according to the present disclosure preferably has a dielectric loss tangent of 0.01 or less, more preferably 0.005 or less, and even more preferably 0.003 or less. The lower limit of the dielectric loss tangent is not particularly limited, but is, for example, 0.0005.
[0141] The average thickness of the laminate is not particularly limited, but from the viewpoints of dielectric tangent and step conformability, it is preferably 5 μm to 90 μm, more preferably 10 μm to 70 μm, and particularly preferably 15 μm to 50 μm.
[0142] The average thickness of the laminate is determined by measuring any five points using an adhesive film thickness meter, for example, an electronic micrometer (product name "KG3001A", manufactured by Anritsu Corporation), and averaging these values.
[0143] <Method of manufacturing laminate> (Film forming) The method for producing the laminate according to the present disclosure is not particularly limited, and known methods can be referred to.
[0144] Suitable film-forming methods include, for example, co-casting, multi-layer coating, co-extrusion, etc. Among these, the co-casting method is preferred.
[0145] When a multilayer structure is produced by a co-casting method or a multi-layer coating method, it is preferable to carry out the co-casting method or the multi-layer coating method using a composition for forming layer A, a composition for forming layer B, a composition for forming layer C, etc., in which the components of each layer are dissolved or dispersed in a solvent.
[0146] Examples of the solvent include halogenated hydrocarbons such as dichloromethane, chloroform, 1,1-dichloroethane, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane, 1-chlorobutane, chlorobenzene, and o-dichlorobenzene; halogenated phenols such as p-chlorophenol, pentachlorophenol, and pentafluorophenol; ethers such as diethyl ether, tetrahydrofuran, and 1,4-dioxane; ketones such as acetone and cyclohexanone; esters such as ethyl acetate and γ-butyrolactone; and ethylene carbonate. Examples of the organic solvent include carbonates such as propylene carbonate and propylene carbonate; amines such as triethylamine; nitrogen-containing heterocyclic aromatic compounds such as pyridine; nitriles such as acetonitrile and succinonitrile; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and urea compounds such as tetramethylurea; nitro compounds such as nitromethane and nitrobenzene; sulfur compounds such as dimethyl sulfoxide and sulfolane; and phosphorus compounds such as hexamethylphosphoramide and tri-n-butylphosphoric acid, and two or more of these may be used.
[0147] As the solvent, since it is less corrosive and easy to handle, a solvent mainly composed of an aprotic compound, particularly an aprotic compound having no halogen atom, is preferred, and the ratio of the aprotic compound to the entire solvent is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass. In addition, as the aprotic compound, since it is easy to dissolve the liquid crystal polymer, it is preferred to use amides such as N,N-dimethylformamide, N,N-dimethylacetamide, tetramethylurea, and N-methylpyrrolidone, or esters such as γ-butyrolactone, and N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone are more preferred.
[0148] In addition, the solvent is preferably a solvent mainly composed of a compound having a dipole moment of 3 to 5, since it is easy to dissolve the liquid crystal polymer. The proportion of the compounds 3 to 5 is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass. As the aprotic compound, a compound having a dipole moment of 3 to 5 is preferably used.
[0149] Furthermore, as the solvent, a solvent mainly composed of a compound having a boiling point of 220° C. or lower at 1 atmospheric pressure is preferred because it is easy to remove, and the proportion of the compound having a boiling point of 220° C. or lower at 1 atmospheric pressure in the entire solvent is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass. As the aprotic compound, it is preferable to use a compound having a boiling point of 220° C. or lower at 1 atmospheric pressure.
[0150] In the method for producing a laminate according to the present disclosure, a support may be used when the laminate is produced by the above-mentioned co-casting method, multi-layer coating method, co-extrusion method, or the like.
[0151] Examples of the support include a metal drum, a metal band, a glass plate, a resin film, and a metal foil. Among these, the support is preferably a metal drum, a metal band, or a resin film.
[0152] The support may have a surface treatment layer formed on its surface so that it can be easily peeled off. The surface treatment layer may be made of hard chrome plating, fluororesin, or the like. The average thickness of the support is not particularly limited, but is preferably from 25 μm to 75 μm, and more preferably from 50 μm to 75 μm.
[0153] The method for removing at least a part of the solvent from the cast or applied film-like composition (coating film) is not particularly limited, and any known drying method can be used.
[0154] (Stretching) The method for producing a laminate according to the present disclosure can be appropriately combined with stretching in terms of controlling molecular orientation and adjusting the thermal expansion coefficient and mechanical properties. The stretching method is not particularly limited, and known methods can be referred to. It may be performed in a state containing a solvent or in a dry film state. Stretching in a state containing a solvent may be performed by gripping the laminate and stretching it, or it may be performed by utilizing autogenous shrinkage due to drying without stretching it. Stretching is particularly effective for the purpose of improving the breaking elongation and breaking strength when the film brittleness is reduced by adding an inorganic filler or the like.
[0155] The laminate according to the present disclosure can be used for various applications, and among others, can be suitably used as a film for electronic components such as printed wiring boards, and can be even more suitably used as a flexible printed circuit board. Moreover, the laminate according to the present disclosure can be suitably used as a liquid crystal polymer film for metal bonding.
[0156] [Wiring board] The wiring board according to the present disclosure comprises a base material, a wiring pattern disposed on at least one surface of the base material, a layer B disposed between the wiring patterns and on the wiring pattern, and a layer A disposed on layer B, wherein layer B has a phase-separated structure including at least two phases, the elastic modulus of layer B at 160°C is 0.60 MPa or less, the elastic modulus G1 at 260°C of a first phase which is one of the at least two phases exceeds 0.10 MPa, and the elastic modulus G2 at 260°C of a second phase different from the first phase is 0.10 MPa or less, and in a cross section along the thickness direction of layer B, the number of regions in the second phase having a length in the thickness direction of 20 μm or more is 140 / mm 2 The following is the result.
[0157] In the wiring board according to the present disclosure, in a cross section along the thickness direction of layer B, the number of regions in the second phase having a length in the thickness direction of 20 μm or more is 140 / mm 2 Since the thickness is less than or equal to 100 mm, it has excellent step conformability and heat resistance.
[0158] <Base material> The material of the substrate is not particularly limited, but preferably contains a resin, more preferably contains a liquid crystal polymer, and is more preferably a liquid crystal polymer film.
[0159] The average thickness of the substrate is not particularly limited, but is preferably from 5 μm to 100 μm, more preferably from 10 μm to 80 μm, and even more preferably from 20 μm to 70 μm.
[0160] <Wiring pattern> The wiring board according to the present disclosure has a wiring pattern on at least one surface of the substrate. Since layer B is disposed between and on the wiring patterns, the wiring pattern is embedded in the wiring board according to the present disclosure. The wiring pattern can be embedded in the wiring board, for example, by the following method. First, a metal layer is formed on the substrate, and the metal layer is etched in a pattern. This results in a substrate with a wiring pattern. Next, the substrate with a wiring pattern and another substrate having layers A and B are layered together such that the wiring pattern in the substrate with a wiring pattern is in contact with layer B. After layering the substrate with a wiring pattern and the other substrate, they may be bonded together or heat fused together. This results in a wiring board with an embedded wiring pattern.
[0161] The material of the wiring pattern is not particularly limited, but is preferably a metal, and more preferably silver or copper.
[0162] The thickness of the wiring pattern is not particularly limited, but is preferably 5 μm to 40 μm, and more preferably 5 μm to 35 μm.
[0163] The thickness of the wiring pattern is measured by cutting the wiring board with a microtome and observing the cut surface with an optical microscope.
[0164] Preferred aspects of Layer A and Layer B included in the wiring board according to the present disclosure are the same as the preferred aspects of Layer A and Layer B included in the laminate according to the present disclosure.
[0165] From the viewpoint of heat resistance, the wiring board according to the present disclosure preferably further includes a layer C in addition to the above-mentioned layer A and layer B, and layer C is preferably disposed on layer A. A preferred embodiment of layer C is the same as a preferred embodiment of layer C that may be included in the laminate according to the present disclosure.
[0166] <Method of Manufacturing Wiring Board> (First aspect) A first aspect of the method for producing a wiring board according to the present disclosure preferably includes a step of superposing the laminate according to the present disclosure on the wiring pattern of a substrate having a wiring pattern, and a step of heating the substrate having a wiring pattern and the laminate according to the present disclosure in a superposed state to obtain a wiring board. The substrate having a wiring pattern and the laminate are superposed so that the wiring pattern of the substrate having a wiring pattern contacts layer B of the laminate.
[0167] -Layering process- In a first aspect of the method for producing a wiring board according to the present disclosure, the laminate according to the present disclosure is superimposed on the wiring pattern of a substrate having a wiring pattern.
[0168] When stacking the laminates, the laminate may simply be placed on the wiring pattern, or the laminate may be pressed onto the wiring pattern by applying pressure.
[0169] The substrate having a wiring pattern may have a wiring pattern formed on only one surface of the substrate, or may have wiring patterns formed on both surfaces of the substrate.
[0170] The substrate with the wiring pattern can be produced by a known method. For example, a metal layer is attached to at least one surface of the substrate to obtain a wiring board including the substrate and the metal layer disposed on at least one surface of the substrate. The substrate with the wiring pattern can be obtained by performing a known patterning process on the metal layer.
[0171] The preferred embodiments of the substrate and the wiring pattern in the substrate having a wiring pattern are the same as those of the substrate and the wiring pattern explained in the section of the wiring board above.
[0172] -Heating process- In a first aspect of the method for producing a wiring board according to the present disclosure, after the above-mentioned overlapping step, the substrate having a wiring pattern and the laminate according to the present disclosure are heated in an overlapped state to obtain a wiring board.
[0173] The heating method is not particularly limited, and can be performed using, for example, a heat press.
[0174] The heating temperature is preferably from 50°C to 300°C, and more preferably from 100°C to 250°C.
[0175] It is preferable to apply pressure during heating, and the pressure is preferably 0.5 MPa to 30 MPa, and more preferably 1 MPa to 20 MPa.
[0176] The heating time is not particularly limited and is, for example, 1 minute to 2 hours.
[0177] (Second aspect) A second aspect of the method for producing a wiring board according to the present disclosure preferably includes the steps of applying a solution for forming layer A onto a support to form layer A, superposing a film according to the present disclosure and a substrate with a wiring pattern on layer A in this order, and heating the support on which layer A has been formed, the polymer film according to the present disclosure, and the substrate with a wiring pattern in a superposed state to obtain a wiring board. The polymer film and the substrate with a wiring pattern are superposed so that the wiring pattern of the substrate with a wiring pattern is in contact with the polymer film.
[0178] Examples of the support include the same supports as those used in the above-mentioned method for producing a laminate.
[0179] The details of the substrate having a wiring pattern are the same as those of the first embodiment.
[0180] The details of the heating step are the same as those in the first embodiment.
[0181] The wiring board according to the present disclosure can be used for various applications, and among them, the wiring board according to the present disclosure can be suitably used for a flexible printed circuit board. EXAMPLES
[0182] The present disclosure will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present disclosure. Therefore, the scope of the present disclosure is not limited to the specific examples shown below.
[0183] Details of the materials used in the preparation of the films and laminates are as follows.
[0184] P1: Aromatic polyesteramide prepared according to the following manufacturing method
[0185] -Synthesis of aromatic polyesteramide P1- Into a reactor equipped with a stirrer, a torque meter, a nitrogen gas inlet tube, a thermometer, and a reflux condenser, 940.9 g (5.0 mol) of 6-hydroxy-2-naphthoic acid, 415.3 g (2.5 mol) of isophthalic acid, 377.9 g (2.5 mol) of acetaminophen, and 867.8 g (8.4 mol) of acetic anhydride were placed, and the gas in the reactor was replaced with nitrogen gas. After that, the temperature was raised from room temperature (23°C, the same below) to 140°C over 60 minutes while stirring under a nitrogen gas stream, and the mixture was refluxed at 140°C for 3 hours. Next, while distilling off by-product acetic acid and unreacted acetic anhydride, the temperature was raised from 150°C to 300°C over 5 hours, and the temperature was maintained at 300°C for 30 minutes. The contents were then removed from the reactor and cooled to room temperature. The resulting solid was pulverized with a pulverizer to obtain a powdered aromatic polyesteramide P1a. The flow initiation temperature of the aromatic polyesteramide P1a was 193°C. The aromatic polyesteramide P1a was a wholly aromatic polyesteramide. The aromatic polyesteramide P1a was heated in a nitrogen atmosphere from room temperature to 160°C over 2 hours and 20 minutes, then heated from 160°C to 180°C over 3 hours and 20 minutes, and held at 180°C for 5 hours to carry out solid-state polymerization, and then cooled. The aromatic polyesteramide P1b was then pulverized in a pulverizer to obtain a powdered aromatic polyesteramide P1b. The flow-initiation temperature of the aromatic polyesteramide P1b was 220°C. The aromatic polyesteramide P1b was heated in a nitrogen atmosphere from room temperature to 180°C over 1 hour 25 minutes, then heated from 180°C to 255°C over 6 hours 40 minutes, and held at 255°C for 5 hours to carry out solid-state polymerization. The resulting mixture was then cooled to obtain a powdered aromatic polyesteramide P1. The flow initiation temperature of the aromatic polyesteramide P1 was 302° C. The melting point of the aromatic polyesteramide P1 was measured using a differential scanning calorimeter and found to be 311° C. The solubility of the aromatic polyesteramide P1 in N-methylpyrrolidone at 140° C. was 1% by mass or more.
[0186] P2: Polyphenylene sulfide (product name "Torelina", manufactured by Toray Industries, Inc.) P3: Polycarbonate (product name "Iupizeta FPC-2136", manufactured by Mitsubishi Gas Chemical Company, Inc.)
[0187] B1: Particles of hydrogenated styrene-isobutylene-styrene block copolymer (product name "SIBSTAR103T-UL", manufactured by Kaneka Corporation) (average particle size: 10 μm, weight average molecular weight: 100,000) B2: Hydrogenated styrene-isobutylene-styrene block copolymer (product name "SIBSTAR103T-UL", manufactured by Kaneka Corporation) particles (average particle size: 25 μm, weight average molecular weight: 100,000) B3: Hydrogenated styrene-isobutylene-styrene block copolymer (product name "SIBSTAR103T-UL", manufactured by Kaneka Corporation) particles (average particle size: 30 μm, weight average molecular weight: 100,000) B4: Polycarbonate particles (product name "Iupizeta FPC-2136", manufactured by Mitsubishi Gas Chemical Co., Ltd.) (average particle size: 10 μm, weight average molecular weight: 60,000) B5: Particles of hydrogenated styrene-isobutylene-styrene block copolymer prepared according to the following manufacturing method A reaction vessel was charged with 452 mL of 1-chlorobutane, 319 mL of hexane, and 0.55 g of 1,4-bis(1-chloro-1-methylethyl)benzene and cooled to -75°C. Then, 5 mg of dimethylacetamide, 2.3 mL of isobutylene, and 0.08 mL of titanium tetrachloride were added and stirred for 1.5 hours. Next, 0.6 g of styrene was added to the reaction solution and stirring was continued for another 60 minutes, after which the contents of the reactor were poured into water and the organic layer and the aqueous layer were separated. After washing with water, the organic layer was poured into a large amount of methanol to precipitate the polymer, and the resulting polymer was vacuum dried at 60°C for 24 hours. The mixture was pulverized in a pulverizer to obtain a powdered hydrogenated styrene-isobutylene-styrene block copolymer B5. The weight average molecular weight of the hydrogenated styrene-isobutylene-styrene block copolymer B5 was 900 and the average particle size was 10 μm.
[0188] B6: Polytetrafluoroethylene particles produced according to the following manufacturing method 70L of deionized water was added to a stainless steel polymerization tank equipped with an agitator, and after removing the air in the tank, 100g of ethane and tetrafluoroethylene (TFE) were added and the temperature was raised to 85°C. Then, TFE was added again and the pressure in the tank was adjusted to 0.8MPa. 250ppm / H2O of ammonium persulfate and 250ppm / H2O of disuccinic acid peroxide were added in the form of an aqueous solution. Polymerization was performed while maintaining the pressure and temperature in the tank at 0.85MPa and 85°C, respectively, and when the amount of TFE supplied reached 12kg, the polymerization reaction was terminated and the pressure in the tank was released to normal pressure. After cooling the tank to room temperature (25°C), the obtained particles were washed with deionized water. The particles were filtered and dried in a hot air circulation dryer at 170°C for 12 hours to obtain polytetrafluoroethylene (PTFE) particles B6. The weight average molecular weight of the obtained PTFE particles was 5,000 and the average particle size was 10μm.
[0189] (Examples 1 to 7, Comparative Examples 1 to 4) A film or laminate was produced by the method described below.
[0190] To prepare a film or a laminate, a solution for forming a layer A and a solution for forming a layer B were prepared.
[0191] - Preparation of solution for forming layer A - N-methylpyrrolidone was added to the materials shown in Table 1 to adjust the solid content concentration to 8 mass %, thereby obtaining a solution for forming layer A.
[0192] - Preparation of solution for forming layer B - The materials shown in Table 1 were mixed in the amounts (mass %) shown in Table 1, and N-methylpyrrolidone was added to adjust the solids concentration to 20 mass % to obtain a layer B forming solution.
[0193] [Preparation of single-sided copper-clad laminate] -Examples 1 and 2, Examples 5 to 7, Comparative Examples 1 to 4- The solution for forming layer B was fed to a slot die coater equipped with a slide coater, and applied to the treated surface of copper foil (product name "CF-T9DA-SV-18", manufactured by Fukuda Metal Foil and Powder Co., Ltd.) by adjusting the flow rate so as to obtain a film thickness of 30 μm. The coating was dried at 40° C. for 4 hours to remove the solvent from the coating. The temperature was then raised from room temperature (25° C.) to 300° C. at a rate of 1° C. / min under a nitrogen atmosphere. Heat treatment was performed by holding at 300° C. for 2 hours to obtain a laminate B in which layer B (film B) was formed on the support. In the obtained laminate B, film B had a phase-separated structure. Similarly, using the layer A forming solution, a laminate A was obtained in which a layer A (film A) was formed on a support. The laminate A and laminate B were overlapped so that film A of the obtained laminate A and film B of laminate B were in contact with each other, and a lamination process was performed for 1 minute using a laminator (product name "Vacuum Laminator V-130", manufactured by Nikko Materials Co., Ltd.) at 140°C and a lamination pressure of 0.4 MPa, to obtain a laminate in which the support, layer A, layer B, and support were laminated in this order. The support on the layer B side was peeled off, and a laminate (single-sided copper-clad laminate) in which the support, layer A, and layer B were laminated in this order was obtained.
[0194] -Examples 3 and 4- The obtained solution for forming layer A and the solution for forming layer B were fed to a slot die coater equipped with a slide coater, and applied to the treated surface of copper foil (product name "CF-T9DA-SV-18", manufactured by Fukuda Metal Foil and Powder Co., Ltd.) by adjusting the flow rate so that the film thickness of layer A was 20 μm and the film thickness of layer B was 30 μm. The coating was dried at 40 ° C for 4 hours to remove the solvent from the coating. Furthermore, the temperature was raised from room temperature (25 ° C) to 300 ° C at 1 ° C / min in a nitrogen atmosphere. A heat treatment was performed by holding at 300 ° C for 2 hours, and a laminate (single-sided copper-clad laminate) in which the support, layer A, and layer B were laminated in this order was obtained. In the obtained laminate, layer B had a phase separation structure.
[0195] [Preparation of 4-layer copper-clad laminate] The prepared single-sided copper-clad laminate was used to overlap the layer B and the support (copper foil) so that they were in contact with each other. Furthermore, the layer B side of the outermost single-sided copper-clad laminate was overlapped with copper foil (product name "CF-T9DA-SV-18", manufactured by Fukuda Metal Foil and Powder Co., Ltd.). This resulted in a laminate in the order of "copper foil, layer A, layer B" / "copper foil, layer A, layer B" / "copper foil, layer A, layer B" / "copper foil, layer A, layer B" / copper foil. Using a laminator (product name "Vacuum Laminator V-130", manufactured by Nikko Materials Co., Ltd.), lamination was performed for 1 minute at 140°C and a lamination pressure of 0.4 MPa to obtain a precursor for a 4-layer copper-clad laminate. Next, the obtained precursor of the four-layer copper-clad laminate was thermocompressed at 230°C and 4 MPa for 60 minutes using a thermocompression bonding machine (product name "MP-SNL", manufactured by Toyo Seiki Seisakusho Co., Ltd.) to produce a four-layer copper-clad laminate.
[0196] [Creating a wiring board] -Preparation of substrate with wiring pattern- Copper foil (product name "CF-T9DA-SV-18", average thickness 18 μm, manufactured by Fukuda Metal Foil and Powder Co., Ltd.) and liquid crystal polymer film (product name "CTQ-50", average thickness 50 μm, manufactured by Kuraray Co., Ltd.) were prepared as a substrate. The copper foil, substrate, and copper foil were stacked in this order so that the treated surface of the copper foil was in contact with the substrate. A laminator (product name "Vacuum Laminator V-130", manufactured by Nikko Materials Co., Ltd.) was used to perform lamination processing for 1 minute under conditions of 140 °C and lamination pressure 0.4 MPa to obtain a precursor of a double-sided copper-clad laminate. Next, a thermocompression bonding machine (product name "MP-SNL", manufactured by Toyo Seiki Seisakusho Co., Ltd.) was used to thermocompress the obtained precursor of the double-sided copper-clad laminate for 10 minutes under conditions of 300 °C and 4.5 MPa to produce a double-sided copper-clad laminate. The copper foil on both sides of the double-sided copper-clad laminate was roughened, and a dry film resist was attached to it. The substrate was exposed to light so that the wiring pattern remained, developed, etched, and the dry film was removed to produce a substrate with a wiring pattern including a ground line and three pairs of signal lines on both sides of the substrate with a line / space of 100 μm / 100 μm. The length of the signal line was 50 mm, and the width was set so that the characteristic impedance was 50 Ω.
[0197] -Making a wiring board- The above-mentioned substrate with a wiring pattern was superimposed on the layer B side of the produced single-sided copper-clad laminate, and hot pressed at 160° C. and 4 MPa for 1 hour to obtain a wiring board. The obtained wiring board had a wiring pattern (ground line and signal line) embedded therein, and the thickness of the wiring pattern was 18 μm.
[0198] The following measurements and evaluations were carried out, and the results are shown in Table 1.
[0199] <<Measurement method>> [Elastic modulus of layer B at 160°C] The cross section of the single-sided copper-clad laminate was exposed using a cryomicrotome. Next, layer B was identified, and the elastic modulus of layer B at 160°C was measured as the indentation elastic modulus using a nanoindentation method. The indentation elastic modulus was measured using a microhardness tester (product name "DUH-W201", manufactured by Shimadzu Corporation) by applying a load with a Vickers indenter at a loading rate of 0.28 mN / sec, holding the maximum load of 10 mN for 10 seconds, and then unloading at a loading rate of 0.28 mN / sec.
[0200] [Elastic modulus of the first and second phases in layer B at 260°C] The cross section of the single-sided copper-clad laminate was exposed using a cryomicrotome. Next, the first and second phases in layer B were identified, and the elastic modulus of the first and second phases at 260°C was measured as the indentation elastic modulus using a nanoindentation method. The indentation elastic modulus was measured using a microhardness tester (product name "DUH-W201", manufactured by Shimadzu Corporation) by applying a load with a Vickers indenter at a loading rate of 0.28 mN / sec, holding the maximum load of 10 mN for 10 seconds, and then unloading at a loading rate of 0.28 mN / sec.
[0201] [Number of large pieces] The second phase was identified from the image obtained by X-ray CT scanning of the single-sided copper-clad laminate. The number of regions with a thickness length of 20 μm or more among the identified second phases was counted. The measurement was performed at 0.05 mm 2 The measurement was carried out at three arbitrary points within the range of 1 mm. The average value was multiplied by 20 to obtain 1 mm. 2 The results were calculated as the number of pieces per unit.
[0202] [Dielectric tangent] The copper foil of a single-sided copper-clad laminate was removed with an aqueous solution of ferric chloride, washed with pure water, and dried to obtain a polymer film, which was then used for the measurement. The dielectric loss tangent was measured at a frequency of 10 GHz by the resonance perturbation method. A 10 GHz cavity resonator (Kanto Electronics Application Development Co., Ltd., "CP531") was connected to a network analyzer (Agilent Technology, Inc., "E8363B"), and the polymer film was inserted into the cavity resonator. The dielectric loss tangent of the film or laminate was measured from the change in resonance frequency before and after insertion for 96 hours under an environment of 25°C temperature and 60% RH.
[0203] <<Evaluation method>> [Step-following ability] The wiring board was cut in the thickness direction with a microtome, and the cross section was observed with an optical microscope. The length L1 of the gap generated in the in-plane direction between layer B and the wiring pattern was measured. The average value for 10 points was calculated. The evaluation criteria are as follows: A: No gaps were found. B: The average value of L1 was less than 1 μm. C: The average value of L1 was 1 μm or more.
[0204] [Heat resistance] The four-layer copper-clad laminate was cut into a size of 30 mm x 30 mm to prepare an evaluation sample. The evaluation sample was treated for 168 hours in a thermohygrostat at a temperature of 85°C and a relative humidity of 85%. The evaluation sample was then placed in an oven set at 260°C and heated for 15 minutes. After heating, the evaluation sample was cut with a razor, and the cross section was observed under an optical microscope to evaluate the state of peeling. A: No distortion of the laminate was observed, and no peeling was observed between Layer B and the copper foil. B: Distortion of the laminate occurred, but no peeling was observed between layer B and the copper foil. C: Peeling was observed between layer B and the copper foil with a width of 1.0 mm or less. D: Peeling was observed between layer B and the copper foil with a width of more than 1.0 mm.
[0205] [Table 1]
[0206] As shown in Table 1, Examples 1 to 8 have a phase-separated structure including at least two phases, an elastic modulus at 160°C of 0.60 MPa or less, an elastic modulus G1 at 260°C of a first phase, which is one of the at least two phases, exceeds 0.10 MPa, an elastic modulus G2 at 260°C of a second phase different from the first phase is 0.10 MPa or less, and the number of regions in the second phase having a length in the thickness direction of the film is 140 / mm 2 Since the thickness was less than 1 mm, it was found that the film had excellent step conformability and heat resistance.
[0207] On the other hand, in Comparative Example 1, the number of regions in the second phase having a length in the thickness direction of 20 μm or more was 140 / mm 2 It was found that the heat resistance was inferior. In Comparative Example 2, the elastic modulus at 160° C. was more than 0.60 MPa, and it was found that the heat resistance was poor. In Comparative Example 3, the number of regions in the second phase having a length in the thickness direction of 20 μm or more was 140 / mm 2 and the elastic modulus at 160° C. was greater than 0.60 MPa, indicating that the step-following ability and heat resistance were poor. In Comparative Example 4, the elastic modulus at 260° C. of both the first phase and the second phase was 0.10 MPa or less, and it was found that the heat resistance was poor.
[0208] In Example 1, the second phase contained a polymer having a weight average molecular weight of 1000 or more, and it was found that, compared with Example 6, the heat resistance was superior.
[0209] It was found that Example 1, in which the second phase contained a thermoplastic elastomer, was superior to Example 5 in terms of step conformability and heat resistance.
[0210] In Example 1, the second phase contained an elastomer containing a structural unit derived from styrene, and it was found that, compared with Example 7, it was superior in the step conformability and heat resistance.
[0211] In Example 1, the proportion of the second phase was 50 mass % or more, and it was found that, compared with Example 8, it was superior in the step conformability and heat resistance.
Claims
1. having a phase-separated structure containing at least two phases, The elastic modulus at 160°C is 0.60 MPa or less, The elastic modulus G1 at 260°C of the first phase, which is one of the at least two phases, is greater than 0.10 MPa; The elastic modulus G2 at 260° C. of the second phase different from the first phase is 0.10 MPa or less; In a cross section along the thickness direction of the film, the number of regions of the second phase having a length in the thickness direction of 20 μm or more is 140 / mm 2 Below is the film.
2. The film of claim 1 , wherein the second phase comprises a polymer having a weight average molecular weight of 1000 or greater.
3. The film according to claim 2 , wherein the polymer having a weight average molecular weight of 1000 or more is a thermoplastic elastomer.
4. The film according to claim 3 , wherein the thermoplastic elastomer is an elastomer containing structural units derived from styrene.
5. The film according to claim 3, wherein the thermoplastic elastomer is at least one selected from the group consisting of a styrene-ethylene-butylene-styrene block copolymer, a styrene-isobutylene-styrene block copolymer, a styrene-ethylene-propylene-styrene copolymer, a styrene-isoprene-styrene block copolymer, and hydrogenated products thereof.
6. The film according to any one of claims 1 to 5, wherein the proportion of the second phase is 50 area % or more in a cross section along the thickness direction of the film.
7. A layer A and a layer B disposed on at least one surface of the layer A, The layer B has a phase-separated structure including at least two phases, The layer B has an elastic modulus of 0.60 MPa or less at 160° C., The elastic modulus G1 at 260°C of the first phase, which is one of the at least two phases, is greater than 0.10 MPa; The elastic modulus G2 at 260° C. of the second phase different from the first phase is 0.10 MPa or less; In a cross section of the layer B along the thickness direction, the number of regions of the second phase having a length in the thickness direction of 20 μm or more is 140 / mm 2 The laminate is as follows:
8. The laminate of claim 7 , wherein the layer A comprises a liquid crystal polymer.
9. The present invention comprises a substrate, a wiring pattern disposed on at least one surface of the substrate, a layer B disposed between the wiring patterns and on the wiring patterns, and a layer A disposed on the layer B, The layer B has a phase-separated structure including at least two phases, The layer B has an elastic modulus of 0.60 MPa or less at 160° C., The elastic modulus G1 at 260°C of the first phase, which is one of the at least two phases, is greater than 0.10 MPa; The elastic modulus G2 at 260° C. of the second phase different from the first phase is 0.10 MPa or less; In a cross section of the layer B along the thickness direction, the number of regions of the second phase having a length in the thickness direction of 20 μm or more is 140 / mm 2 The wiring board is shown below.
Citation Information
Patent Citations
Liquid crystal polymer film and substrate for high-speed communication
WO2021060455A1
Polymer film, multilayer body and method for producing same
WO2022163776A1